2023
DOI: 10.1007/s13165-023-00432-7
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges of bio-based fertilizers utilization for improving soil health

Abstract: Bio-based fertilizers (BBFs) have been promoted as a solution to help manage bio-waste problems and improve soil health conditions. Their potential is to replace mineral fertilizers due to nonrenewable energy dependency and the accumulation that threatens environmental issues. Currently, laboratory and field-based literature have been growing since European Union (EU) looks BBFs as the future of agriculture bio-based products. Nevertheless, it is worth to summarizing the results on a regular basis. The added v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“… 2 This warrants the need to use biostimulants or biofertilizers that can boost the plant productivity. 4 Different biostimulants, such as amino acids and hydrolyzates, were obtained from plants, animals, microorganisms, and industrial by-products that when applied improved the plant growth. 1 , 9 In this study, exogenous application of plant-derived smoke (SMK) and BGD slurry on potato is reported that improved the photosynthetic parameters, pigments, growth, and altered genome-wide methylation profile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2 This warrants the need to use biostimulants or biofertilizers that can boost the plant productivity. 4 Different biostimulants, such as amino acids and hydrolyzates, were obtained from plants, animals, microorganisms, and industrial by-products that when applied improved the plant growth. 1 , 9 In this study, exogenous application of plant-derived smoke (SMK) and BGD slurry on potato is reported that improved the photosynthetic parameters, pigments, growth, and altered genome-wide methylation profile.…”
Section: Discussionmentioning
confidence: 99%
“… 3 One of the resource efficient approaches is to employ the bio-based agents (biostimulants) that can positively stimulate the physiological processes of plants. 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil health index (SHI) could integrate different types of physical, chemical, and biological variables into a composite index that is widely used for evaluating soil health. SHIs have been developed for evaluating the influence of different field management measures [15][16][17] or different land use types [18][19][20][21] on soil properties, revealing their impact on soil productivity and ecosystem function [22][23][24][25][26]. SHI was often used to evaluate the influences of the ecosystem, such as the soil quality after deforestation in Northern Iran or ecological risk by soil heavy metal pollution [27].…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to the need to assess the nutrient use efficiency of BBFs and RENURE fertilizers in valid comparisons with synthetic fertilizers, as well as the need to further investigate their environmental impacts 3 . The microbial composition of BBFs may also deserve more attention, as BBFs can contain pathogens, depending on their source and on their production processes 8 . Recovery processes during the production of BBFs might also be detrimental and could potentially eliminate ubiquitarian beneficial microorganisms for soil that were present in the source material, because of high temperatures and/or the presence of toxic compounds at high concentration.…”
Section: Introductionmentioning
confidence: 99%